Analisis Efektivitas dan Efisiensi Pengelolaan Keuangan Desa di Desa Maregam Kecamatan Tidore Selatan Kota Tidore Kepulauan Pada Masa Pandemi Covid-19 - Rahmat Hidayat; E. Hartaty Hadady; Abdul Rahman Jannang (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the level of effectiveness and efficiency of Village Fund management in Maregam Village during the Covid-19 Pandemic. This type of research is descriptive quantitative. The data collection technique used in this research is to copy the village budget realization report file. The research method used is descriptive quantitative method using a secondary data analysis approach with nonparametric test equipment using the Wilcoxon Test. The results showed that the level of effectiveness of village financial management based on an average effectiveness ratio of 98.33% was included in the